Integrating Artificial Intelligence in Secondary Education: A Comparative Study of Pedagogical Readiness and Student Engagement in Southeast Asia - Suryadi, A. Fitriani; Amrulloh, M. Sholahuddin; Yani, H. Ahmad; Dinarni, Dian; Afrizal, Afrizal (PT Inovasi Pratama Internasional, 2025)
The integration of Artificial Intelligence (AI) in secondary education has emerged as a pivotal trend across Southeast Asia, promising transformative impacts on pedagogy and student engagement. This qualitative comparative study analyzes pedagogical readiness and student engagement among secondary schools in selected Southeast Asian countries—including Indonesia, Singapore, and Thailand. Data were acquired through semi-structured interviews, thematic analysis, and document reviews. The results indicate that while AI-driven teaching practices enhance personalization and engagement, significant disparities remain in teacher competencies, infrastructure, and policy implementation. The findings highlight the urgent need for comprehensive professional development, equitable digital infrastructure, and culturally responsive curricula to harness AI's potential in education